Gendered Access to Finance: The Role of Team Formation, Idea Quality, and Implementation Constraints in Business Evaluations - Vojtech Bartos; Silvia Castro; Kristina Czura; Timm Opitz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We analyze gender discrimination in entrepreneurship finance. Access to finance is crucial for entrepreneurial success, yet constraints for women are particularly pronounced. We structurally unpack whether loan officers evaluate business ideas and implementation constraints differently for male and female entrepreneurs, both as individual entrepreneurs or in entrepreneurial teams. In a lab-in-the-field experiment with Ugandan loan officers, we document gender discrimination of individual female entrepreneurs, but no gender bias in the evaluation of entrepreneurial teams. Our results suggest that the observed bias is not driven by animus against female entrepreneurs but rather by differential beliefs about women's entrepreneurial ability or implementation constraints in running a business. Policies aimed at team creation for start-up enterprises may have an additional benefit of equalizing access to finance and ultimately stimulating growth.
Keywords: C93; G21; J16; L25; L26; O16; 330; access to finance; gender bias; entrepreneurship; lab-in-the-field